(3aJM GdgGOj Ydi HYV CdaGX GdfXe hGHf ZGRj hGdeQGOjs - (3YHO GdQMef Hf EOQjS Hf eMeO GdefLQj GdEOQjSj GdMSfj GdJdeSGfj GdaGSjs; (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, CHh eMeO, HOQ GdOjf, GdeYQha HGHf Ce bGSe,J (B749 (3g` s ((3YHOGdbGOQ Hf YHOGdbGOQ Hf GdWjH Hf eMeO CeZGQ s)
(3ChdgG (B:s
(3hHYO, adeG enqf Gddg Ydj HbQGAI CdajI GHf eGdc GdJj gj GdTQjYI ef ChVM GdeSGdc s
(3BNQgG (B:s
(3hajg JTHjg GdLYd HGdabQ ef GdeGd hbO bjd Ef GdYde NjQ QRb QRbfG Gddg GdYed Hg GfJgJ MGTjI GdTjN s
(3Vef eLehY , JQJjHgG (B: (3ef U (B49 - (3U(B506s
(3hHBNQgG NGJeI aj HYV TjhN GdeUfa aj fMh hQbJjf hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs